Simulation modelling and analysis of balance mechanisms of innovation search in innovation network. (21st April 2020) - Xie, Linling; Wei, Tie
Based on the scale-free weighted dynamic network, this paper proposes an agent-based model to investigate the dynamics characterising the interaction between balance mechanisms of innovation search and the innovation network. Specifically, it explores how two balance mechanisms of innovation search, punctuated equilibrium and ambidexterity, influence the evolution of the growth of network knowledge and performance through the simulation of the three-stage innovation search processes in the innovation network. In addition, it considers and assesses the impact of the rate of knowledge diffusion. The results show that the balance mechanisms of innovation search and the innovation network are co-evolutionary. The balance mechanisms of innovation search have an impact on the growth of network knowledge and performance, and the rate of knowledge diffusion has a contingent effect. This study provides a valid theoretical analysis framework and approach for future research in balance mechanisms of search.